Does otolith organ dysfunction influence outcomes after a customized program of vestibular rehabilitation? - Murray, K.; Hill, Keith; Phillips, B.; Waterston, J. (2010)
BACKGROUND AND PURPOSE: Vestibular rehabilitation (VR) is a successful approach to the treatment of vestibular dysfunction. The purpose of this study was to investigate the influence of otolith dysfunction on the response to VR in individuals with a peripheral vestibular disorder. PARTICIPANTS AND METHODS: Eighteen participants with loss of semicircular canal function only, and 29 participants with combined loss of semicircular canal and otolith organ function were recruited. All participants received a comprehensive clinical assessment before and after an 8-week customized program of VR. RESULTS: Both groups achieved significant improvements on most measures at the end of the 8-week VR program. However, no significant differences were identified between participants with versus without otolith dysfunction with respect to change in symptom severity (P = .81), self-perceived handicap (P = .92), functional limitations (P = .93), or balance performance after VR. DISCUSSION AND CONCLUSIONS: Otolith dysfunction does not significantly influence the response to rehabilitation of individuals with a peripheral vestibular disorder. Vestibular rehabilitation is associated improvements in symptom severity, self-perceived handicap, and balance function in individuals with otolith dysfunction. Copyright © 2010 Neurology Section, APTA.